A study of rice blast disease in Kampung Sawah Sempadan, Selangor. / Ahmad Ghazali Rahim - Rahim, Ahmad Ghazali (Faculty of Plantation and Agrotechnology, 2016)
Production of rice are facing another problem which are pest and disease. One of the disease problem that comes up from rice production is rice blast caused by Pyricularia oryzae. Rice blast could be the one of the major disease that have been found in Kampung Sawah Sempadan, Selangor, which tropics environment help of causing of varying degrees of damage. In this study, information regarding to the incidence, severity and occurrence factor of blast disease in Kampung Sawah Sempadan, Selangor during hot climate or drought season were recorded. Result show there are significant diferrent (p - value < 0.05) for both percentage incidence and severity between the selected field except for mean incidence in field 3 and mean of severity in field 1. There are several factor that contribute to the occurrence of the disease such as cultural practices by the farmers and environmental factor.